Integrative population pharmacokinetic and pharmacodynamic dose finding approach of the new camptothecin compound namitecan (ST1968). (3rd June 2015) - Joerger, M.; Hess, D.; Delmonte, A.; Gallerani, E.; Fasolo, A.; Gianni, L.; Cresta, S.; Barbieri, P.; Pace, S.; Sessa, C.
<x xml:space="preserve">Abstract</x> Aims Namitecan is a new camptothecan compound undergoing early clinical development. This study was initiated to build an integrated pharmacokinetic (PK) and pharmacodynamic (PD) population model of namitecan to guide future clinical development. Methods Plasma concentration–time data, neutrophils and thrombocytes were pooled from two phase 1 studies in 90 patients with advanced solid tumours, receiving namitecan as a 2 h infusion on days 1 and 8 every 3 weeks (D1, 8) (n = 34), once every 3 weeks (D1) (n = 29) and on 3 consecutive days (D1–3) (n = 27). A linear three compartment PK model was coupled to a semiphysiological PD‐model for neutrophils and thrombocytes. Data simulations were used to interrogate various dosing regimens and give dosing recommendations. Results Clearance was estimated to be 0.15 l h–1, with a long terminal half‐life of 48 h. Body surface area was not associated with clearance, supporting flat‐dosing of namitecan. A significant and clinically relevant association was found between namitecan area under the concentration–time curve (AUC) and the percentage drop of neutrophils (r2 = 0.51, P < 10−4) or thrombocytes (r2 = 0.49, P < 10−4). With a target for haematological dose‐limiting toxicity of <20%, the recommended dose was defined as 12.5 mg for the D1, 8 regimen, 23 mg for the once every 3 week regimen and 7 mg for the D1–3 regimen. Conclusion This is the first integrated population PK–PD analysis of the new hydrophilic topoisomerase I inhibitor namitecan, that is currently undergoing early clinical development. A distinct relationship was found between drug exposure and haematological toxicity, supporting flat‐dosing once every 3 weeks as the most adequate dosing regimen.